2016
DOI: 10.1038/srep18969
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain alterations in primary open angle glaucoma: a 3T MRI study

Abstract: Glaucoma is not only an eye disease but is also associated with degeneration of brain structures. We now investigated the pattern of visual and non-visual brain structural changes in 25 primary open angle glaucoma (POAG) patients and 25 age-gender-matched normal controls using T1-weighted imaging. MRI images were subjected to volume-based analysis (VBA) and surface-based analysis (SBA) in the whole brain as well as ROI-based analysis of the lateral geniculate nucleus (LGN), visual cortex (V1/2), amygdala and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 51 publications
5
60
2
4
Order By: Relevance
“…Studies have shown that the glaucoma-associated neurodegeneration process is not limited to the optic nerve, but involves the whole visual pathway extending to the lateral geniculate nucleus and visual cortex [7][8][9], as demonstrated by MRI imaging showing a reduction in height and volume of the LGN in subjects with POAG [10] and NTG [11]. Similarly, fMRI studies have confirmed alterations in the visual cortex that correlate with the visual field changes observed in glaucoma [10,12].…”
Section: Introductionmentioning
confidence: 79%
“…Studies have shown that the glaucoma-associated neurodegeneration process is not limited to the optic nerve, but involves the whole visual pathway extending to the lateral geniculate nucleus and visual cortex [7][8][9], as demonstrated by MRI imaging showing a reduction in height and volume of the LGN in subjects with POAG [10] and NTG [11]. Similarly, fMRI studies have confirmed alterations in the visual cortex that correlate with the visual field changes observed in glaucoma [10,12].…”
Section: Introductionmentioning
confidence: 79%
“…Structural MRI studies have revealed a significantly shorter optic chasm height and reduced optic nerve diameter in glaucoma patients versus normal controls [203]. Neurodegenerative changes in the LGN, as evidenced by reduction in LGN height and volume, is also reported in POAG patients using voxel-based morphometry and diffusion tensor imaging, with some evidence emerging to suggest that the extent of atrophy may correlate with disease severity [183]. A reduced LGN volume is also reported in patients with NTG versus age-matched controls, which may indicate a shared pathology in the brain [203].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…In addition to LGN atrophy, a reduction in volume of the optic radiations and primary visual cortex is documented in patients with POAG [183]. There is some evidence to suggest that a loss of grey matter density occurs in the calcarine sulcus and primary visual cortex in response to prolonged sensory deprivation (AMD and glaucoma patients versus age-matched controls) [14].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…In fact, NTG cases represent about 25–32% of overall POAG cases, both in the Beaver Dam study in Wisconsin, USA [Klein et al, ] and in the Egna Neumarkt study in Alto Adige, Italy [Bonomi et al, ] whereas NTG prevalence is three to four times higher than HTG in Japan [Shiose et al, ]. In POAG with raised IOP, we and others have previously demonstrated through multimodal brain MRI widespread damage of diffusion tensor imaging (DTI)‐derived anatomical connectivity (AC), gray matter (GM) atrophy and/or altered resting state functional connectivity (FC) that can go beyond the visual system, even since the early disease stage [Dai et al, ; Frezzotti et al, ; Jiang et al, ; Wang et al, ; Zikou et al, ].…”
Section: Introductionmentioning
confidence: 99%